Geochemistry and petrogenesis of sanukitoids and high-K anatectic granites from the Bundelkhand Craton, India: Implications for late-Archean crustal evolution. (1st May 2019) - Singh, Pradip K.; Verma, Sanjeet K.; Singh, Vinod K.; Moreno, Juan A.; Oliveira, Elson P.; Mehta, Pankaj
Highlights: There are sanukitoids and anatectic granites in the Bundelkhand Craton. U-Pb zircon dating of a sanukitoid yielded a crystallization age of 2577 ± 16 Ma. Sanukitoids are derived from a crustal source. Sanukitoids and anatectic granites formed in a subduction-collision environment. Abstract: In this paper, we present in situ zircon U–Pb ages as well as whole-rock elemental and Sm-Nd isotopic compositions for late Archean sanukitoids of the Bundelkhand Craton, India. The LA–ICP–MS zircon U–Pb dating results of the sanukitoids (s.l.) indicate that these rocks were emplaced at 2577 ± 16 Ma, with inherited zircon at an age of 2644 ± 25 Ma, and are coeval with high-K anatectic granites (2544–2583 Ma). The sanukitoids (s.l.) are characterized by high-alumina (15–16 wt.%), Mg# (27–50) and TiO2 (0.31–0.87 wt.%). They have a strongly enriched signature in terms of incompatible trace elements (LREEs and LILE) pointing to a subduction-related or crustal source. The high-K anatectic granites are characterized by Al2 O3 (12–15 wt.%), Mg# (13–39) and TiO2 (0.06–0.8 wt.%); they have enriched and variable concentrations of LILEs and REEs; and negative Eu anomalies (Eu/Eu* = 0.15–0.93). The whole-rock εNd (t) values (−3.64 to −1.66) indicate a crustal component. These isotopic and geochemical characteristics indicate that the sanukitoid plutons originated from the mixing of metasomatized mantle melts with anatectic melts and were followed by homogenization at shallow levels of emplacement, whereas the high-K anatectic granites indicate reworking of the pre-existing TTG crust during the cratonic stabilization ca. 2.5 Ga. This interpretation suggests a temporal evolution from TTG-domination through sanukitoids (s.l.) to anatectic leucogranites by an internal reworking of the continental crust, involving subduction-collision environments in the late Archean era. Such magmatic events and tectonics during the late-Archean in the Bundelkhand Craton resemble other Archean cratons, such as the Dharwar, North China, Karelian, Superior Province, Pilbara, Kaapvaal and Amazonian.